Architecture of Culotta & Leone for the Historic Centre of Cefalù: plan, project, execution - Giuseppe Di Benedetto; Maria Luisa Germanà (Techne, 2016)
Architectural interventions in historical contexts throughout most of the 20th century were inter-linked by the two extremes of conservation and transformation. In the 1980s, in Italy, an important step forward was taken along the theoretical and operational path towards the approach as demanded by the current and future conditions of historical urban areas: long-term strategy oriented; more responsible; multi-scale and including the entire contemporary urban settlement. The experience of Culotta & Leone in the Historic Centre of Cefalù may well constitute a unicum, as a result of their particular anchoring to the social context, and yet it offers an interesting example of continuity (between plan, architectural design and execution) that gave substance to architectural solutions which may be seen as an evolving continuity of the historical remains.